Comparative interpretation of the characters in English and Uzbek novels - Sattorovna, Jamilova Bashorat; Yusufovna, Kakharova Mohigul (The journal of contemporary issues in business and government, 2021)
This article is about the characters in Uzbek and English literature prose .The literary description of children‟s spiritual world, the psychology of heroes, reflection of character‟ thinking and images, the position, ways of psychologism in children‟s literature. It discusses the problems of teenagers‟ psychology in Uzbek and English children's realistic novels.